Context-aware diabetic patient remote monitoring using wearable and mobile App / Mohd Izzat Ismail Hashim - Ismail Hashim, Mohd Izzat (2019)
The rise of busy lifestyle has made it difficult for caregivers to effectively remote monitor diabetic patients when they are away from them. With recent advancement of smartphone and wearable technology, it would improve the adoption of mobile healthcare. Previous studies have shown that context-aware techniques have been widely used in healthcare application. This paper introduces a context-aware android mobile application, titled LoveHealth, with smartwatch integration that would be use by diabetic patients and caregivers. The goal of this mobile application is to provide a tool for caregivers to remote monitor diabetic patients, even when they are not nearby. Context-aware algorithm is applied in this application, where a criticality reading threshold is defined, classifying the readings criticality levels. By applying this algorithm, LoveHealth is able to detect critical glucose reading, which are inputted by the patients manually, or heartrate readings captured from the patients' smartwatch, and notifies their respective caregivers, informing them that they require medical attention. Once the app has been developed, testing is done to ensure each functionality works as expected. Also, the app undergoes one-week evaluation period by real diabetic patients to get their feedback and recommendations regarding the app.